Interdisciplinary teambuilding in management research - Shavkun, Iryna; Dybchynska, Yana (Management and Entrepreneurship: Trends of Development, 2025)
The interdisciplinary approach in science, education and practice has acquired particular importance over the past decade, characterized by the rapid development of technological innovations, increasing uncertainty of the external environment and large-scale changes in the political, economic and social spheres. The aim of this article is to identify the most effective methods for creating interdisciplinary teams to study management problems. To achieve this goal, it is necessary to solve several problems: establish the main attributes of the formation of interdisciplinary teams; study the content, organizational structure and methodological aspects of the formation of interdisciplinary teams; identify the key problems and advantages that arise when creating interdisciplinary teams; determine the most important competencies of the participants that contribute to the successful implementation of a scientific project in the context of interdisciplinary interaction. General scientific methods are employed to support the theoretical arguments and validate the conclusions. The systematic approach enables an understanding of the nature and functional role of teambulding in interdisciplinary management research. Key findings indicate that modern management research requires the integration of knowledge from various disciplines, which makes the process of forming an interdisciplinary team especially important. Interdisciplinary team building is a complex but manageable process, the success of which depends on a conscious approach to the formation, management and motivation of participants. JEL Classification: А 12, B 41, M 10, M 11